Incorporation of biochemical factors for survival analysis of transarterial chemoembolization in patients with hepatocellular carcinoma: A retrospective cohort study. Issue 10 (October 2019) - Chan, Wen-Hui; Huang, Song-Fong; Lee, Chao-Wei; Wu, Tsung-Han; Pan, Kuan-Tse; Lin, Shi-Ming; Yu, Ming-Chin; Hung, Chien-Fu
Introduction: Hepatocellular carcinoma (HCC) is a common gastrointestinal cancer that occurs worldwide, and conventional transarterial chemoembolization (cTACE) is one of the first treatment choices for advanced HCC. However, biochemical factors and comorbidity have seldom been reported in the long-term outcomes. Methods: This retrospective cohort study included 444 HCC patients who underwent cTACE-based therapy in 2010 to 2012. Survival outcomes were analyzed using a Kaplan–Meier curve and Cox regression analysis. Results: The mean age was 62.1 ± 12.5 years, and 74.3% were men. Analysis of the mean biochemical values indicated that the presence of portal vein thrombosis, α-fetoprotein (AFP) >200 ng/mL, AJCC 7th stage III, diabetes, albumin <3 g/dL, and hemoglobin were significantly and independently associated with poorer long-term outcomes. Discussion: The presence of venous thrombus and elevation of AFP levels are the most important factors in cTACE treatment. The host factors, including metabolic status and liver damage, should be evaluated in these patients.